Geospatial Analysis of Landslide Susceptibility and Zonation in Shahpur Valley, Eastern Hindu Kush using Frequency Ratio Model: Geospatial Analysis of Landslide Susceptibility - Rahman, Ghani; Atta-ur-Rahman; Samiullah; Collins, Andrew E. (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
This study dealt with geospatial analysis of Landslide Susceptibility (LS) and resultant zonation in Shahpur valley, eastern Hindu Kush (HK) using Frequency Ratio Model (FRM). Geologically, HK region constitutes the youngest mountain system. In the study area, landslide is a recurrently occurring natural event. Every year, landslides incur significant property and human losses. The extent of damages is expected to multiply in future due to overgrazing, deforestation, increase in population and infrastructural expansion over the fragile slopes. In the HK region, Shahpur valley was selected as the test area to apply FRM using geospatial technique and explore various factors for determining LS. Initially, a reconnaissance field survey was conducted for preparation of landslide inventory map. SPOT5 pan sharpened image of 2.5 m was used to map various sizes of activated landslides and its subsequent locations were verified in the field. The selected LS factors including surface geology, slope gradient, proximity to fault lines, land use, slope aspect, proximity to roads and proximity to stream/river were used. The relationship between landslide and determining factors were spatially analyzed using FRM. As a result, the Frequency Ratio Score (FRS) was calculated for each factor. Based on cumulative FRS, landslide Susceptibility Indices (LSI) were developed and classified into very high, high,moderate, low and very low LS zones. The central part of the valley was found to be highly susceptible to landslide hazard as both natural and anthropogenic factors were prevalent in this region. Finally, the LS zones were validated by the success rate curve approach.